2021
DOI: 10.1108/lthe-08-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of service quality in Saudi universities: the SERVPERF model

Abstract: Purpose The purpose of this study is to examine the influence of service quality on student’s satisfaction. Design/methodology/approach Using empirical research, the study identified previously validated scales of service quality and student satisfaction. Using the SERVPERF scale, data were collected from 279 students studying in public and private universities across Saudi Arabia. The model fit of the scale was assessed to ensure that the data produced accurate outcomes. Structural equation modelling was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
(61 reference statements)
4
13
0
Order By: Relevance
“…The choice between SERVQUAL and SERVPERF metrics for service quality measurement is often subjective (Rodrigues et al, 2011). The SERVQUAL scale possesses higher diagnostic power to pinpoint areas for improvement, whereas the SERVPERF metrics are more efficiently administered (Sohail and Hasan, 2021). Silva et al (2017) and Sydorov et al (2020) suggest that evaluating for validity, reliability, and methodological soundness of service quality the SERVPERF scale is superior for these metrics.…”
Section: Methodology Research Instrumentmentioning
confidence: 99%
“…The choice between SERVQUAL and SERVPERF metrics for service quality measurement is often subjective (Rodrigues et al, 2011). The SERVQUAL scale possesses higher diagnostic power to pinpoint areas for improvement, whereas the SERVPERF metrics are more efficiently administered (Sohail and Hasan, 2021). Silva et al (2017) and Sydorov et al (2020) suggest that evaluating for validity, reliability, and methodological soundness of service quality the SERVPERF scale is superior for these metrics.…”
Section: Methodology Research Instrumentmentioning
confidence: 99%
“…The findings also indicate a direct and significant positive relationship between perceived service quality and satisfaction. These results support the previous studies applicable for both traditional and online learning methods [17,37,41,42,94]. Therefore, the significant impact of SERVQUAL dimensions on perceived quality and satisfaction suggest their importance in achieving competitiveness, greater value, growth of service opportunities, and satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…To highlight the importance of system and information quality, Uppal et al [39] included learning content and course website with the SERVQUAL model and found a positive correlation between the student perception of ELQ with tangibility, responsiveness, assurance, learning content, and course website. This study is based on the theoretical foundations of e-service quality in the context of e-commerce, which has been applied by many researchers in the field of e-learning to measure the satisfaction level of e-learners [37,[39][40][41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the limitations cited above, a school of researchers (Akdere et al. , 2020; Cronin and Taylor, 1994; Sohail and Hasan, 2021) prefer SERVPERF over SERVQUAL. In contrast to the expectation vs. perceived performance measure of SERVQUAL, SERVPERF adopts a purely performance-based approach to measuring service quality.…”
Section: Literature Reviewmentioning
confidence: 99%